Arginine Enhancement of Cell Dissociation in Suspension-Cultured of Aromatic Rice Cells (Oryza sativa L. var Khao Dawk Mali 105) - Nitsri Sangduen; Pranot Klamsomboon (Agriculture and Natural Resources, 2002)
Suspension culture of Oryza sativa L. var. Khao Dawk Mali 105 was initiated from embryogenic region of callus derived from mature seeds cultured in the modified N6 medium supplemented with 1 mg/l 2,4-dichlorophenoxyacetic acid (2,4-D), 0.25 mg/l kinetin, 2 % sucrose, 5 mM proline and various nitrogen sources. Three types of suspension-cultured medium (SM) with the supplementation of inorganic nitrogen (SM1), or organic nitrogen plus arginine (SM2), or inorganic nitrogen plus arginine (SM3) were used.The suspension-cultured of rice callus in the SM gave cytoplasmically dense cell and homogeneous aggregation cell size larger than 1 mm, while those in the SM2 produced cytoplasmically clear cell and aggregated cell size smaller than 1 mm. The addition of arginine to SM with inorganic nitrogen (SM3) seemed to combine the desirable characters of finely dispersed cell aggregate and cytoplasmically dense cell. It was revealed by scanning electron micrographs indicating a difference in intercellular layer while cultured in 1 mM arginine containing SM medium was less deeply embedded in intercellular layer than in arginine-free medium. A finely dispersed cell suspension was obtained from rice callus tissue in SM supplemented with 1mM arginine. These results suggested that the suspension-cultured medium with inorganic nitrogen plus arginine should be suitable for generating an established suspension cell line for selection experiment as well as protoplast isolation.